2012
DOI: 10.1038/aps.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

Breast regression protein-39 (BRP-39) promotes dendritic cell maturation in vitro and enhances Th2 inflammation in murine model of asthma

Abstract: Aim: To determine the roles of breast regression protein-39 (BRP-39) in regulating dendritic cell maturation and in pathology of acute asthma. Methods: Mouse bone marrow-derived dendritic cells (BMDCs) were prepared, and infected with adenovirus over-expressing BRP-39. Ovalbumin (OVA)-induced murine model of acute asthma was made in female BALB/c mice by sensitizing and challenging with chicken OVA and Imject Alum. The transfected BMDCs were adoptively transferred into OVA-treated mice via intravenous injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…While the role of BRP-39 in fungal asthma has not been previously investigated, study of Chi3l1 À/À mice in ovalbumin (OVA) and house dust mite (HDM) models of asthma reported decreased airway resistance (improved lung function) (16). In an alternative study design where bone marrow-derived dendritic cells overexpressing BRP-39 were transferred into mice that subsequently underwent the OVA asthma model, BRP-39 was also found to drive AHR (51). OVA and HDM models of asthma primarily drive a Th2 asthma phenotype, whereas the fungal asthma model employed here attempts to recapitulate a particular endotype of human asthma (severe asthma with fungal sensitization).…”
Section: Discussionmentioning
confidence: 99%
“…While the role of BRP-39 in fungal asthma has not been previously investigated, study of Chi3l1 À/À mice in ovalbumin (OVA) and house dust mite (HDM) models of asthma reported decreased airway resistance (improved lung function) (16). In an alternative study design where bone marrow-derived dendritic cells overexpressing BRP-39 were transferred into mice that subsequently underwent the OVA asthma model, BRP-39 was also found to drive AHR (51). OVA and HDM models of asthma primarily drive a Th2 asthma phenotype, whereas the fungal asthma model employed here attempts to recapitulate a particular endotype of human asthma (severe asthma with fungal sensitization).…”
Section: Discussionmentioning
confidence: 99%
“…This result demonstrates their evolutionarily conserved roles as innate defense systems. Chitinase 3-like 1 (Chi3l1), also known as breast regression protein 39 (BRP-39), has been more emphasized in cancer and lung inflammation due to human homolog YKL-40, which is mainly expressed in breast cancer cells and lung macrophages 6 , 10 12 . In Streptococcus pneumoniae infections, Chi3l1 regulates macrophage cell death to promote bacterial clearance, indicating a function in innate immunity against pathogens 13 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a controversy with regard to the biological functions of YKL-40. In the past, YKL-40 was shown to be induced during T2 inflammation through an IL-13 dependent mechanism [5153]. On the contrary, recent studies by Gomez and James suggested that YKL-40 and chitotriosidase were not T2-specific biomarkers in airway diseases [20, 22].…”
Section: Discussionmentioning
confidence: 99%